Teaching German as A Foreign Language After English in A Russian-Speaking Context - Tolybayeva Guljamila Orazbayevna (Web of Journals Publishing, 2023)
The article considers the features of teaching German as a foreign language after learning English. It is shown that students who have already mastered English as a first foreign language require less effort to learn German as a second foreign language. The difficulties in learning German as a second foreign language are revealed, and the advantages are noted that should serve as an incentive for students to learn German. Examples of the influence of previously studied English on German are given at the level of semantics, spelling, morphology, etc. The article concludes that it is necessary in the process of teaching German as a second foreign language to use knowledge of English productively.